2002
DOI: 10.1038/sj.sc.3101389
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exercise training in persons with spinal cord injury: effects on strength, arm ergometry performance and psychological well-being

Abstract: Study design: Randomized controlled trial of exercise training in persons with spinal cord injury. Objective: The purpose of this study was to examine the e ects of 9 months of twice-weekly exercise training on strength, arm ergometry performance, and indices of psychological wellbeing and quality of life. Setting: Centre for Health Promotion and Rehabilitation, McMaster University, Hamilton, Ontario, Canada. Methods: Thirty-four men and women (aged 19 ± 65 years) with traumatic spinal cord injury (C4 ± L1; AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
380
4
18

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 465 publications
(418 citation statements)
references
References 35 publications
16
380
4
18
Order By: Relevance
“…6 In a 9-month randomized control trial (RCT) conducted in our centre, we found that regular aerobic and resistance training may reduce these health concerns in individuals with SCI regardless of the level or completeness of the injury. 7 We also found that despite their immobility, dependence on others for transporta-tion, and high susceptibility to illness, individuals with SCI may adhere to an exercise training programme outside of their own home with rates comparable to those found for the population at large. Specifically, their dropout rate over the 9-month RCT (48%) was very similar to the 50% dropout rate frequently cited for the able bodied.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…6 In a 9-month randomized control trial (RCT) conducted in our centre, we found that regular aerobic and resistance training may reduce these health concerns in individuals with SCI regardless of the level or completeness of the injury. 7 We also found that despite their immobility, dependence on others for transporta-tion, and high susceptibility to illness, individuals with SCI may adhere to an exercise training programme outside of their own home with rates comparable to those found for the population at large. Specifically, their dropout rate over the 9-month RCT (48%) was very similar to the 50% dropout rate frequently cited for the able bodied.…”
Section: Introductionsupporting
confidence: 65%
“…In spite of the fact that the individuals in the exercise group reported less pain after the 9-month RCT than did the nonexercising controls, they were not pain free. 7 Our results suggested that the degree of pain after the 9-month RCT accounted for 83% of the variability in exercise adherence in our seven participants during the 3-month follow-up. When examining the relation between pain and exercise adherence, it is difficult to determine whether perceptions of pain cause decreases in exercise adherence or, alternately, if decreases in exercise participation cause increases in the perception of pain.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations